Phase I trial of WEE1 inhibition with chemotherapy and radiotherapy as adjuvant treatment, and a window of opportunity trial with cisplatin in patients with head and neck cancer: the WISTERIA trial protocol - Martin Forster; Joseph Sacco; Christina Yap; Kevin Harrington; Hisham Mehanna; Anthony Kong; James Good; Amanda Kirkham; Joshua Savage; Rhys Mant; Laura Llewellyn; Joanna Parish; et al. (BMJ Open)
Introduction Patients with head and neck squamous cell carcinoma with locally advanced disease often require multimodality treatment with surgery, radiotherapy and/or chemotherapy. Adjuvant radiotherapy with concurrent chemotherapy is offered to patients with high-risk pathological features postsurgery. While cure rates are improved, overall survival remains suboptimal and treatment has a significant negative impact on quality of life.Cell cycle checkpoint kinase inhibition is a promising method to selectively potentiate the therapeutic effects of chemoradiation. Our hypothesis is that combining chemoradiation with a WEE1 inhibitor will affect the biological response to DNA damage caused by cisplatin and radiation, thereby enhancing clinical outcomes, without increased toxicity. This trial explores the associated effect of WEE1 kinase inhibitor adavosertib (AZD1775).Methods and analysis This phase I dose-finding, open-label, multicentre trial aims to determine the highest safe dose of AZD1775 in combination with cisplatin chemotherapy preoperatively (group A) as a window of opportunity trial, and in combination with postoperative cisplatin-based chemoradiation (group B).Modified time-to-event continual reassessment method will determine the recommended dose, recruiting up to 21 patients per group. Primary outcomes are recommended doses with predefined target dose-limiting toxicity probabilities of 25% monitored up to 42 days (group A), and 30% monitored up to 12 weeks (group B). Secondary outcomes are disease-free survival times (groups A and B). Exploratory objectives are evaluation of pharmacodynamic (PD) effects, identification and correlation of potential biomarkers with PD markers of DNA damage, determine rate of resection status and surgical complications for group A; and quality of life in group B.Ethics and dissemination Research Ethics Committee, Edgbaston, West Midlands (REC reference 16/WM/0501) initial approval received on 18/01/2017. Results will be disseminated via peer-reviewed publication and presentation at international conferences.Trial registration number ISRCTN76291951 and NCT03028766.